2017
DOI: 10.1063/1.4983329
|View full text |Cite
|
Sign up to set email alerts
|

Foam Au driven by 4ω–2ω ignition laser pulse for inertial confinement fusion

Abstract: Green light (2ω) has the potential to drive ignition target for laser fusion with significantly more energy than blue light (3ω) and a relatively higher damage threshold for the optic components in the final optic assembly, but it has issues of a relatively low laser to x-ray conversion efficiency and a hard x-ray spectrum as compared to 3ω. In this paper, we propose to drive a foam hohlraum wall with an ignition laser pulse by taking a 4ω laser at the pre-pulse and a 2ω laser at the main-pulse, called as 4ω -… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In 2003 and subsequently in 2005, Hammer and Rosen proposed to use low density gold foam material for the hohlraum cavity useful in reduction of wall loss and consequently enhancement of x-ray emission yield [32,33] and thereafter, a few experiments on enhancement of x-rays by gold foam targets are reported. The CE of laser to x-ray is investigated for low density gold foam target using 1D hydrodynamic theoretical simulation and several experiments are performed [23,[34][35][36]. The authors reported an enhancement of CE for 0.1 g/cc Au in comparison to solid gold.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003 and subsequently in 2005, Hammer and Rosen proposed to use low density gold foam material for the hohlraum cavity useful in reduction of wall loss and consequently enhancement of x-ray emission yield [32,33] and thereafter, a few experiments on enhancement of x-rays by gold foam targets are reported. The CE of laser to x-ray is investigated for low density gold foam target using 1D hydrodynamic theoretical simulation and several experiments are performed [23,[34][35][36]. The authors reported an enhancement of CE for 0.1 g/cc Au in comparison to solid gold.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a series of experiments of the Spherical Hohlraum Campaign (SPHC) have been performed on the ShenGuang laser facilities in Shanghai and Mianyang in China to test its performance (Huo et al 2016a, b;Xie et al 2016;Chen et al 2017;Li et al 2017c;Shu et al 2018). Finally, it is proposed to use 2ω lasers for future ignition facilities with a configuration designed for the octahedral spherical hohlraum and to use a foam wall to increase the coupling efficiency from the laser to the capsule (Lan and Song 2017;.…”
Section: Inertial Confined Fusion Driven By Lasersmentioning
confidence: 99%
“…Recently, a hollow-walled hohlraum (I-Raum) was designed to reduce the growth of the gold bubble and stabilize the gold-gas interface [18]. Experimental results showed that the implosion core has been more prolate for the I-Raum compared to the cylinder hohlraum [19].…”
Section: Introductionmentioning
confidence: 99%